2018
DOI: 10.1111/jbfa.12319
|View full text |Cite
|
Sign up to set email alerts
|

The recent financial crisis, start‐up financing and survival

Abstract: We investigate the effects of the recent financial crisis on start‐up financing and survival using a dataset that covers all Belgian new business registrations between 2006 and 2009. We find that bank debt is the single most important source of funding, even for start‐ups founded during the crisis. However, start‐ups founded in crisis years use less bank debt and have a higher likelihood of bankruptcy, even after controlling for their creditworthiness. These effects are stronger for start‐ups that are more dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 72 publications
(140 reference statements)
1
16
0
Order By: Relevance
“…Based on extant literature, the results we have presented on the negative impact of the recession on young firms are, if anything, underestimated. Recent contributions have indicated that start-ups founded in recessionary years have a higher probability of going bankrupt, relative to start-ups founded in nonrecessionary years ( Deloof and Vanacker, 2018 ). Huber et al (2017) , who use Austrian data and adopt a methodology similar to ours, find that young firms decrease their employment growth during the Great Recession when considering firms conditional on survival.…”
Section: Discussionmentioning
confidence: 70%
“…Based on extant literature, the results we have presented on the negative impact of the recession on young firms are, if anything, underestimated. Recent contributions have indicated that start-ups founded in recessionary years have a higher probability of going bankrupt, relative to start-ups founded in nonrecessionary years ( Deloof and Vanacker, 2018 ). Huber et al (2017) , who use Austrian data and adopt a methodology similar to ours, find that young firms decrease their employment growth during the Great Recession when considering firms conditional on survival.…”
Section: Discussionmentioning
confidence: 70%
“…The practice of using digital equipment, platform solutions and software on leasing terms has already become widespread. Digital startups are becoming increasingly popular [16]. The construction industry is already a consumer of developed digital technologies [17].…”
Section: The Content Of the International Financial Leasing Transactionmentioning
confidence: 99%
“…In the case of firm survival is startup capital, previous studies based on firm survival often highlight the important role played by financial capital (Cooper et al, 1994), so that in the case of new firms, one would anticipate higher levels of financial capital at startup would improve a firm's chances of survival because so they have more time to access additional sources of capital before their startup capital runs out (Liao et al, 2008;Parker and Belghitar, 2006), while startups founded in crisis years useless bank debt and have a higher likelihood of bankruptcy (Deloof and Vanacker, 2018).…”
Section: Internal Determinants Of Firm's Survivalmentioning
confidence: 99%